Effect of industrial waste metal chips on flexural behavior of re-inforced concrete beams - Aslan, Çağatay; Karagöz, Ömer; Gökdemir, Hande; Günaydın, Ayten (Revista de la Construcción. Journal of Construction, 2023)
Recycling waste and by-products are necessary for environmentally friendly production and reducing carbon footprint. It is possible to use waste materials as additives and admixtures to improve the strength, ductility, and toughness of the reinforced concrete (RC) elements. Industrial waste metal chips have a high potential to be used as an admixture which improves the general behavior of RC elements, as proven by preliminary studies. In this study, various industrial waste metal chips were added into concrete as an admixture in different sizes and proportions to experimentally investigate the effect on the flexural strength of RC beams. Five RC beam specimens with identical dimensions and different metal chip waste admixtures were cast for the experiments. The load-displacement behavior of beams was examined by conducting a three-point bending test. As a result, it has been observed that the use of waste metal chips can significantly increase the flexural strength and ductility of the beams. The maximum load of one specimen with steel chip admixture is found to be 1.75 times higher than the waste-free reference beam. It is concluded that the usage of waste metal chips as an admixture is a viable solution to enhance the flexural behavior of the RC beams.